Cyberbullying on social networking sites: a literature review and future research directions - Chan, Tommy K. H. (Information & management, 2021)
Cyberbullying on social networking sites is an emerging societal issue that has drawn significant scholarly attention. The purpose of this study is to consolidate the existing knowledge through a literature review and analysis. We first discuss the nature, research patterns, and theoretical foundations. We then develop an integrative framework based on social cognitive theory to synthesize what is known and identify what remains to be learned, with a focus on the triadic reciprocal relationships between perpetrators, victims, and bystanders. We discuss the key findings and highlight opportunities for future research. We conclude this paper by noting research contributions and limitations